1) Using the quadratic equation x² – 4x – 5 = 0, perform the following tasks:
a) Solve by factoring.
Answer:
x = -1, 5
Show work in this space.
x² – 4x – 5 = 0
(x – 5)(x + 1) = 0
x = -1, 5
b) Solve by using the quadratic formula.
Answer:
x = -1, 5
Show work in this space
x² – 4x – 5 = 0
ax² + bx + c = 0
So a = 1, b = -4, c = -5
x = [(-b) ± √(b² – 4ac)]/(2a)
= [-(-4) ± √((-4)² – 4*1*(-5))]/(2*1)
= [4 ± √(16 + 20)]/2
= [4 ± 6]/2
= 5, -1
2006-12-16 08:39:46
·
answer #1
·
answered by Wal C 6
·
0⤊
2⤋
Factoring x^2 - 4x - 5 =0 X^2 -5x + x -5 =0 (x-5)(x+1)=0 x=5,-1 Quadratic b^2-4ac = 16+20 = 36 x=(4+sqrt(36))/2 and (4-sqrt(36))/2 = 10/2 and -2/2 = 5 and -1
2016-03-28 21:28:39
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
x2 – 4x – 5 = 0
(x - 5) (x + 1) = 0
So x = +5 or x = -1
For the quadratice equation:
a = 1, b = -4, c = -5
Sqrt b^2 - 4ac = sqrt (16 - (4 * 1 * -5)) = sqrt (16 - (-20)) = sqrt (36) = +6 or -6
The quadratic equation is then:
[- (-4) +/- 6 ]/ 2 = 2 +/- 3 = +5 or -1
2006-12-16 08:40:18
·
answer #3
·
answered by Renaud 3
·
0⤊
0⤋
a. (x-5)(x+1) = 0
Therefore: (x-5) = 0 and (x+1) = 0
so x = 5 or x = -1
b. The quadratic formula is x = (-b ± sqrt( b^2 - 4ac)) / 2a
where ax^2 + bx + c is the form of the equation.
So for your equation it is best represented as:
1x^2 + -4x + -5
Now plug it into the equation and we get:
(-(-4) ± sqrt ( (-4)^2 - 4(1)(-5))) / 2(1)
(-(-4) ± sqrt( 16 - (-20))) / 2
(4 ± sqrt( 16 + 20)) / 2
(4 ± sqrt(36)) /2
(4 ± 6) / 2
So now we have 2 answers:
(4+6) / 2 and (4 - 6) / 2
which is 10 / 2 = 5 and -2 / 2 = -1
2006-12-16 08:50:13
·
answer #4
·
answered by Mark T 1
·
0⤊
1⤋
By factoring, the equation becomes (x+1)(x-5).
Using the quadratic formula, x = -1 or 5
Facotring: Guess and Check Method
(x+_)(x-_)
(x+1)(x-5)
Check: Distributes to x^2 - 4x - 5.
Quadratic Formula:
a = 1
b = -4
c = -5
x = [-b (+ -) the suqare root of (b^2 - 4ac)]/2a
x = [4 (+ -) the square root of (16+20)]/2
x = [4 (+ -) the square root of 36]/2
x = [4 (+ -) the square root of 36]/2 = [4 (+ -) 6]/2
x = -2/2 or 10/2 = -1 or 5
2006-12-16 08:48:27
·
answer #5
·
answered by Anonymous
·
0⤊
1⤋
Factoring
x² - 4x - 5
(x - 5)(x + 1)
Roots
X = 5
x = - 1
- - - - - - - - - -
x² - 4x - 5
a = 1
b = -4
c = - 5
- - - - - - - - - -
Quadratic Formula
x = - b ± √b² - 4ac / 2a
x = - (-4) ± √(- 4)² - 4(1)(- 5) / 2(1)
x = 4 ± √16 - (- 20) / 2
x = 4 ± √16 + 20 / 2
x = 4 ± √36 /2
x = 4 ± 6 / 2
x = 2 ± 3
x = 5
x = - 1
- - - - - - - -s-
2006-12-16 10:19:39
·
answer #6
·
answered by SAMUEL D 7
·
0⤊
1⤋
a) (x-5)(x+1)
work: (1)(x2)-4x-5
(1)(-5)= -5
-5x + 1x = -4x
(x-5)(x+1)
b) (-b +- (b2-4ac)1/2)/2a
-(-4)+-((-4)2-4(1)(-5)1/2)/2(1)
4+-(36)1/2/2
4+-6/2
10/2, -2/2
5, -1
ps - the numbers after the parenthesis are the exponents, and the 1/2 is the square root. +- is plus as well as minus
2006-12-16 08:38:59
·
answer #7
·
answered by soccerswim88888 1
·
0⤊
0⤋
By factoring, use FOIL : (x-5)(x+1) = 0 and find what makes each factor equal zero.
By QF, which is -b +- sqrt (b^2 - 4ac) all over 2a,
a = 1, b = -4 and c = -5 so plug these numbers into the formula and see what you get.
2006-12-16 08:33:59
·
answer #8
·
answered by hayharbr 7
·
0⤊
1⤋
(x+1)*(x-5)=0 from here you get x1= -1 and x2=5
2006-12-16 09:07:10
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋
(x-4)(x-1)=0
x-4=0, x=4
x-1=0, x=1
2006-12-16 08:42:30
·
answer #10
·
answered by Care 1
·
0⤊
1⤋